From Courtroom to Classroom: Operationalizing "Adequacy" in Funding Teaching and Learning - Bruce S. Cooper; Tim DeRoche; William G. Ouchi; Carolyn Brown (Educational Considerations, 2004)
A quality, standards-based reform would provide a framework and system of accountability that elevates the most possible number of our students to acquisition of an academic foundation and allows students the greatest number of future academic options and careers.